Ein Bericht zum World Café „Quo vadis, Geographiedidaktik?” im Rahmen des DKG 2023 - Raschke, Nicole; Brockmüller, Svenja; Eberth, Andreas; Hanke, Melissa; Mehren, Rainer; Meurel, Melissa; Ohl, Ulrike; Pettig, Fabian (Journal of Geography Education, 2024)
The report summarises the results of the World Café "Quo vadis, Geography Didactics?" at the DKG 2023 in Frankfurt. Thematically, the results relate to (1) understanding of research and research methods, (2) current research trends, (3) theory-practice transfer, (4) blind spots and challenges of geographical didactics research and (5) perspectives for future geographical didactics research.